Strategi Dinas Pemuda Olahraga dan Pariwisata Dalam Pengembangan Potensi Pariwisata Kabupaten Paser - Claudia Cristanty; Muhammad Jamal Amin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to find out and describe the strategies carried out by the Paser Regency Youth, Sports, and Tourism Department in developing Tourism Potential with a research focus on organizational strategies, programs, supporting resources, and institutions that support the development of tourism potential. This type of research is descriptive qualitative using methods namely observation, interviews, documentation, and library research. In this research, the analysis components used are data collection, data reduction, data presentation, and conclusions or verification. Based on the results of research conducted at the Paser Regency Youth, Sports, and Tourism Department, it focus on improving institutional strategies developed to manage, organize, and run tourism itself by maximizing visitor visits. This is one of the strategies of the Youth, Sports, and Tourism Department in developing tourism, which still requires attention to the development of infrastructure and resources, both natural and human, and requires a lot of support to be able to develop tourism potential well.